Modelling the magnetic field configuration of neutron stars. Issue 6 (August 2014) - Ciolfi, R.
Abstract The properties of the extremely strong magnetic fields of neutron stars affect in a unique way their evolution and the associated phenomenology. Due to the lack of constraints from direct observations, our understanding of the magnetic field configuration in neutron star interiors depends on the progress in theoretical modelling. Here we discuss the effort in building models of magnetized neutron stars focussing on some of the recent results. In particular, we comment on the instability of purely poloidal and purely toroidal magnetic field configurations and on the evidence in favour of the so‐called twisted‐torus solutions. We conclude with an outlook on the present status of the field and future directions. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)